A Key Space Enhanced Chaotic Encryption Scheme for Physical Layer Security in OFDM-PON - Meihua Bi; Xiaosong Fu; Xuefang Zhou; Lu Zhang; Guowei Yang; XueLin Yang; Shilin Xiao; Weisheng Hu (IEEE Photonics Journal)
In this paper, we propose a key space enhanced chaos-based encryption scheme with no requirement of redundant sideband information in an orthogonal frequency division multiplexing passive optical network (OFDM-PON). For the first time, a simple 1-D chaotic logistic map is employed to scramble the chaotic subcarrier allocation both in time/frequency domain and logical operation, which provides a huge key space to enhance the physical layer confidentiality. Due to the dynamic chaotic permutations, the largest key space is achieved in comparison with the reported encryption schemes in OFDM-PON. In addition, a ∼10-Gb/s secure transmission with encrypted OFDM data is experimentally demonstrated over 25-km standard single-mode fiber. The proposed encryption scheme demonstrates the excellent security of data transmission in OFDM-PON and the robustness against exhaustive attacks.